Alcohol and Illicit Drug Use Among Young People Exposed to Armed Conflict: A Systematic Review and Meta-Analysis - Ghimire, Satchit (My University, 2026)
Young people exposed to armed conflict are at an increased risk of alcohol and illicit drug use. However, evidence on this topic is limited and inconsistent. This review examined the prevalence, risk, and protective factors of alcohol and illicit drug use among young people exposed to armed conflict by systematically synthesising the available evidence. We searched three databases (PubMed, PsycINFO, and Web of Science) and supplemented them with a manual search. Peer-reviewed articles published in English from 1980 to 2025 on alcohol or illicit drug use among young people aged 10–24, exposed to armed conflict, were included. The Joanna Briggs Institute (JBI) critical appraisal checklist was used to assess risk of bias. Data analyses were done using random-effects meta-analysis and narrative synthesis. This review followed PRISMA guidelines. We screened 2,229 studies, out of which 20 were included. The last 30-day pooled prevalence of alcohol use was 17% (95% CI: [8, 27], I² = 99%), whereas the last 30-day prevalence of illicit drug use ranged from 1.5% to 27%. Cannabis, inhalants, cocaine, ecstasy, amphetamines, and tranquillisers were the commonly reported illicit drugs. Male gender, older age, mental health conditions, interpersonal violence, and accessibility were potential risk factors. Family or school support and religion were reported as possible protective factors. Alcohol and illicit drug use are prevalent among armed conflict-exposed young people and are influenced by a multitude of factors. These findings have important public health and research implications. More studies with prospective designs and mixed-method approaches are needed.
Keywords: young people; armed conflict; alcohol; illicit drugs